Virulence potential of biofilm-producing Staphylococcus pseudintermedius, Staphylococcus aureus and Staphylococcus coagulans causing skin infections in companion animals - Andrade, Mariana (2022)
Research Areas: Infectious Diseases ; Pharmacology & Pharmacy